Development of a parent-reported screening tool for avoidant/restrictive food intake disorder (ARFID): Initial validation and prevalence in 4-7-year-old Japanese children. (1st January 2022) - Dinkler, Lisa; Yasumitsu-Lovell, Kahoko; Eitoku, Masamitsu; Fujieda, Mikiya; Suganuma, Narufumi; Hatakenaka, Yuhei; Hadjikhani, Nouchine; Bryant-Waugh, Rachel; Råstam, Maria; Gillberg, Christopher
Abstract: The prevalence of avoidant/restrictive food intake disorder (ARFID) in the general child population is still largely unknown and validated screening instruments are lacking. The aims of this study were (1) to investigate the prevalence of children screening positive for ARFID in a Japanese birth cohort using a newly developed parent-reported screening tool, (2) to estimate the prevalence of children with ARFID experiencing physical versus psychosocial consequences of their eating pattern, and (3) to provide preliminary evidence for the validity of the new screening tool. Data were collected from 3728 4-7-year-old children born between 2011 and 2014 in Kochi prefecture, Japan (response rate was 56.5%); a sub-sample of the Japan Environment and Children's Study (JECS). Parents completed a questionnaire including the ARFID screener and several other measures to assess convergent validity. The point prevalence of children screening positive for ARFID was 1.3%; half of them met criteria for ARFID based on psychosocial impairment alone, while the other half met diagnostic criteria relating to physical impairment (and additional psychosocial impairment in many cases). Sensory sensitivity to food characteristics (63%) and/or lack of interest in eating (51%) were the most prevalent drivers of food avoidance. Children screening positive for ARFID were lighter in weight and shorter in height, they showed more problem behaviors related to mealtimes and nutritional intake, and they were more often selective eaters and more responsive to satiety, which together provides preliminary support for the validity of the new screening tool. This is the largest screening study to date of ARFID in children up to 7 years. Future studies should examine the diagnostic validity of the new ARFID screener using clinically ascertained cases. Further research on ARFID prevalence in the general population is needed.